Do worsening scleroderma capillaroscopic patterns predict future severe organ involvement? a pilot study. Issue 10 (8th March 2012) - Smith, Vanessa; Decuman, Saskia; Sulli, Alberto; Bonroy, Carolien; Piettte, Yves; Deschepper, Ellen; de Keyser, Filip; Cutolo, Maurizio
Abstract : Objective: Assessment of associations of nailfold videocapillaroscopy (NVC) scleroderma patterns ('early', 'active' and 'late') with future severe clinical involvement in a systemic sclerosis (SSc) population. Methods: Sixty-six consecutive patients with SSc according to the LeRoy and Medsger criteria underwent NVC assessment at baseline. Videocapillaroscopic images were classified into 'normal', 'early', 'active' or 'late' NVC pattern. Clinical evaluation was performed for nine organ systems (general, peripheral vascular, skin, joint, muscle, gastrointestinal tract, lung, heart and kidney) according to the disease severity scale of Medsger (DSS) at 18–24 months of follow-up. Severe clinical involvement was defined as category 2–4 per organ of the DSS. Results: NVC patterns were significantly associated with future severe, peripheral vascular/lung involvement at 18–24 months. The OR rose steadily throughout the patterns. The OR for future severe peripheral disease based on simple/multiple (correcting for disease duration, subset and medication) logistic regression was 2.49/2.52 (95% CI 1.33 to 5.43, p=0.003/1.11 to 7.07, p=0.026) for early, 6.18/6.37 for active and 15.35/16.07 for late NVC scleroderma patterns versus the normal NVC pattern. The OR for future severe lung involvement based on simple/multiple regression was 2.54/2.33 (95% CI 1.40 to 5.22, p=0.001/1.13 to 5.52, p=0.021) for early, 6.43/5.44 for active and 16.30/12.68 for late NVC patterns. Conclusions: This pilot study is the first demonstrating an association between baseline NVC patterns and future severe, peripheral vascular and lung involvement with stronger odds according to worsening scleroderma patterns. This may indicate a putative role of capillaroscopy as a biomarker.